ROBOT PENDETEKSI API MENGGUNAKAN BAHASA PEMROGRAMAN BASIC STAMP - Kalsum, Toibah Umi; Trianggana, Dimas Aulia; Hermawansyah, Hermawansyah (UNIVED Press, 2013)
Control is closely related to the strategy that enables a computer acts as the brain in the control system directs the movements of a tool of control , and received a response from the sensor which is owned by the controlled apparatus to the computer . Robots are electro - mechanical or bio - mechanical , or a combination of equipment that generates autonomous movement or by movement commanded . Robotics world is not separated from the control ( control ) . Although it can move on its own , in the end had to move in a controlled manner , either controlled by humans , as well as himself. In this case a microcontroller acts as the memory storage in the form of instructions that have been fed . In the mobile robot instructions filled into memory microcontroller via a serial port so that the robot can move in a stand alone ( stand alone ) without having to be controlled through the computer again because his instructions had been stored in the memory of the microcontroller so that the robot can move the car looking for the source of a fire and extinguish it The microcontroller is a digital electronic device that has inputs and outputs as well as control of the programs that can be written and erased in a special way , the workings of the actual microcontroller to read and write data . The microcontroller can also be called a computer inside the chip used to control electronic devices . The microcontroller can thus be regarded as a kind of microprocessor . Keywords : Robot fire